Development of high performance electrochemical capacitor: A systematic review of electrode fabrication technique based on different carbon materials - Mohd Abid, Mohd Asyadi Azam; Abdul Manaf, Nor Syafira; Bistamam, Mohd Shahril Amin (The Electrochemical Society, 2013)
Increasing demand for energy requirement has attracted considerable attention among researchers to develop efficient energy storage device. Among energy storage devices, electrochemical capacitor (EC) has great potential for its capability to deliver more power than batteries and store more energy than conventional capacitors. The electrode or active material is the most crucial factor in determining the device properties. Recently, carbon based materials play significant roles as electrode materials and possesses remarkably significant achievements toward the development of sustainable energy storage applications. Electrode fabrication technique is another important factor to be considered. Hence, this article reviews the electrode fabrication techniques for EC based on different types of carbon as electrode materials, and their EC performances measured by techniques such as cyclic voltammetry and charge discharge characteristics are also discussed.